POLA HUBUNGAN PATRON-CLIENT KIAI DAN SANTRI DI PESANTREN - Syamsul Ma'arif (Ta'dib: Jurnal Pendidikan Islam, 2010)
Pesantren as a unique of Indonesian Islamic  education institution has a dynamic in its development. Although modernization and its implication has been influenced pesantren’s existence, it can survive until noweday. One of factors support pesantren is figure of kiai as a strong leader with his patronage system. This is a relation pattern which has been rooted in pesantren tradition. The system has widely networks and disseminated by kiai not only in the pesantren, but also out of it. Patron-client between santri and kiai legitimize the authority and charisma of kiai. It also make him easy to influence and ask community to participate in buillding pesantren. Last but not least, the community it self have a good awareness and attitude (sami’na wa atha’na) in foolowing and supporting every single of kiai’s policy for advance of pesantren.